1998
DOI: 10.1021/es970636z
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes in a Dissolved Soil Humic Acid during Photochemical Degradation Processes under O2and N2Atmosphere

Abstract: Irradiation (UV/Vis λ > 290 nm) under nitrogen and oxygen atmosphere significantly affected the structure of dissolved humic material (DHM). Photobleaching of the DHM solution occurred essentially under O 2 atmosphere in conjunction with a decrease in average molecular weight and an increase in acidity due to the disaggregation and photooxidation processes. The structural changes were followed by various separation and analytical methods including capillary zone electrophoresis (CZE), gel permeation chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
114
4

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(127 citation statements)
references
References 68 publications
9
114
4
Order By: Relevance
“…Although DOC photodegradation has been well documented in a number of aquatic systems (e.g., Mopper et al 1991), measurements of light effects on DON or C/N are scarce (Jørgensen et al 1998). In one notable study, with a concentrated solution of humic material isolated from a loamy soil, Schmitt-Kopplin et al (1998) observed that organic carbon was lost at a significantly more rapid rate than organic nitrogen, oxygen, or hydrogen when exposed to UV radiation under an O 2 atmosphere. Structural differences in DOM molecules resulted in different rates of photodegradation, with lignins and lipids degrading rapidly as compared to carbohydrates, alkylbenzenes, and N-containing structures (Schmitt-Kopplin et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although DOC photodegradation has been well documented in a number of aquatic systems (e.g., Mopper et al 1991), measurements of light effects on DON or C/N are scarce (Jørgensen et al 1998). In one notable study, with a concentrated solution of humic material isolated from a loamy soil, Schmitt-Kopplin et al (1998) observed that organic carbon was lost at a significantly more rapid rate than organic nitrogen, oxygen, or hydrogen when exposed to UV radiation under an O 2 atmosphere. Structural differences in DOM molecules resulted in different rates of photodegradation, with lignins and lipids degrading rapidly as compared to carbohydrates, alkylbenzenes, and N-containing structures (Schmitt-Kopplin et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In one notable study, with a concentrated solution of humic material isolated from a loamy soil, Schmitt-Kopplin et al (1998) observed that organic carbon was lost at a significantly more rapid rate than organic nitrogen, oxygen, or hydrogen when exposed to UV radiation under an O 2 atmosphere. Structural differences in DOM molecules resulted in different rates of photodegradation, with lignins and lipids degrading rapidly as compared to carbohydrates, alkylbenzenes, and N-containing structures (Schmitt-Kopplin et al 1998). Direct photolysis of carboxyl groups (e.g., Zafiriou et al 1984) may account for the bulk of the photolabile DOC pool, while cleavage of inorganic N functionalities from DOM is likely to occur by a less direct process.…”
Section: Discussionmentioning
confidence: 99%
“…A photocatalyst harnesses UV radiation from sunlight or artificial light and uses the energy to break down different substances including organic materials, organic acids, estrogens, pesticides, dyes, crude oil, microbes (including viruses) and chlorine resistant organisms, inorganic molecules such as nitrous oxides (NO x ) and, in combination with precipitation or filtration, can also remove metals such as mercury [13][14][15]. Due to this universal applicability, photocatalysis with nanoparticles as catalysts is used to reduce air pollution, in building materials, for self-cleaning surfaces in addition to water purification.…”
Section: Mechanism Of Semiconductor Catalysismentioning
confidence: 99%
“…This has a significant implication for developing nations. It can also improve the quality of the water released from water treatment plants by assisting traditional treatment methods to target more substances and thereby obtain a higher efficiency of the whole process [14][15][16].…”
Section: Societal Impact Of Photocatalysismentioning
confidence: 99%
“…Moreover, Component 5 (tryptophan-like) was less degradable (26 ± 9%, n = 3) than the unidentified Component 4 (54 ± 6%, n = 3, probably autochthonous DOM) as well as Components 1 and 2 (Stedmon et al, 2007a; Table 1). The significant increase of the fluorescence of the unidentified Component 6 may derive from the photoproducts of DOM, and possibly from the aromatic compounds originated upon photoirradiation of fulvic and humic acids (Corin et al, 1996;Schmitt-Kopplin et al, 1998).…”
Section: Photochemical Behavior Of Fdom In the Aquatic Environmentmentioning
confidence: 99%